Designing Creative Cities/Districts Within The Framework Of New Urban Agenda - Arif Sugiono; Prasetya Nugeraha (Institute of Computer Science (IOCS), 2022)
As an emerging industry, the creative industry is increasingly showing its urgency and relevance. Even in various cities/regencies in Indonesia, this industry is able to be a new engine of growth in line with the new urban agenda. Using the method of literature study, observation and documentation, this paper focuses on describing how to build a creative industry ecosystem through the formation of Creative Cities / Regencies and the challenges faced